#TITLE_ALTERNATIVE# - ASHAQ DARUSSALAM (NIM 10107064); Pembimbing : Dr. Kuntjoro Adji S., AJAR
Colebook-White equation is a formula to calculate fluid friction factor in turbulent flow. This equation is implicit and not easy to be solved. The usual method to solve this equation is recursive method. Calculation by this method is already accurate but requires many iterations to reach convergent results. Here, Colebrook-White equation is solved using Lambert-W function and the new functions. The solution of this new function is more robust, accurate, and efficient than Colebrook-White solution expressed in term of Lambert-W function. MATLAB code is provided.